Evaluasi Ketrampilan Menyimak Dengan Memanfaatkan Permainan Berbisik Berantai Dalam Pembelajaran Bahasa Arab - Aizzatin Habibah; Syihabuddin Syihabuddin (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2021)
Evaluation is the activity of a program in order to find out its achievements and the level of efficiency of its implementation. This evaluation is one of the important components in the process of teaching and learning activities. Arabic learning evaluation activities especially in listening skill usually still use instruments in general, where it causes the children bored and stressed in facing tests. Actually evaluation activities can be done in an interesting and enjoyable methods such as games. For example we can use chain whisper games. The purpose of this study is to introduce a method through a game that can be used to evaluate listening skill in Arabic learning. With the chain whisper games, the teacher is expected to provide a test atmosphere that can motivate students to be more interesting, they can do activities in a relax and enjoy, but the teacher can assess student achievement. This research process uses qualitative research based on library research.